Reappraisal and lectotypification of Justicia tanalensis S. Moore (Acanthaceae), rediscovered from central Madagascar more than 100 years since the last collection - Onjalalaina, Guy. E.; Jiang, Hui; Rakotonasolo, Andrimalala R.; Wanga, Vincent Okelo; Hu, Guang-Wan (Phytotaxa, 2022)
Justicia tanalensis (Acanthaceae) was rediscovered from the central highland of Madagascar since the last collection in 1895. Its morphological characters are reported and amended with photographs in this paper. The species is characterized by a prostrate herbaceous habit and a simple spike with one flower per node. It has a distribution range in the central-eastern Madagascar. The conservation assessment of the species is provided. Because no holotype was indicated in the protologue and the type specimens cited by the original author were collected in two different times, they should be considered as two gatherings and they are syntypes. The lectotype specimen of the name is designated here as well.